Relationship between the full moon and the incidence of vaginal premature delivery in a level III hospital in Lima, Peru - Saldaña-Díaz, Claudia (2023)
Objective. To determine the association between the full moon and the incidence of vaginal preterm deliveries among women with vaginal delivery in a tertiary care hospital in Lima, Peru. Methods. An analytical cross-sectional study was carried out on a secondary data of the Certificate of Live Birth (CNV) of Peru. All newborns from the National Maternal Perinatal Institute were studied between the years 2013 and 2021. The duration of the full moon phase was determined through the programming language with Python 3.6 and the analysis of the incidence of prematurity with the STATA v15 statistical package. Results. 90,653 newborns were selected from the CNV national data, of which 11,563 (12.75%) participants were born during the days of the full moon and 79,089 (87.25%) during the other phases. A higher incidence of vaginal preterm births was observed during the full moon phase, compared to other phases (p<0.001). Multivariate analysis found that the full moon had a 1.17% higher mean value of incidence of vaginal preterm birth adjusted for year compared to the other phases (IC 95% 1.050 - 1.292, p<0.01). Conclusion. A higher incidence of vaginal preterm births was found during the full moon phase in the study population. These results should be taken with caution as induced births were included in the analysis.